2018
DOI: 10.1038/s41398-018-0346-9
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in association of symptoms and white matter deficits in first-episode and drug-naive schizophrenia

Abstract: Accumulating evidence shows that disruption of white matter (WM) may be involved in the pathophysiology of schizophrenia, even at the onset of psychosis. However, very few studies have explored sex difference in its association with psychopathology in schizophrenia. This study aims to compare sex differences in clinical features and WM abnormalities in first-episode and drug-naive (FEDN) schizophrenia among Han Chinese inpatients. The WM fractional anisotropy (FA) values of the whole-brain were determined usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 75 publications
1
19
0
Order By: Relevance
“…Previous studies that focused on sex differences in chronic SZ patients showed more negative symptoms but fewer positive symptoms in males than females [7,9]. In this study, we found that sex differences in patients with first-episode SZ were significant only in terms of negative symptoms, as found in some other studies [8,37]. However, several studies reported no sex differences in symptoms among ANFE patients with SZ [38,39].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Previous studies that focused on sex differences in chronic SZ patients showed more negative symptoms but fewer positive symptoms in males than females [7,9]. In this study, we found that sex differences in patients with first-episode SZ were significant only in terms of negative symptoms, as found in some other studies [8,37]. However, several studies reported no sex differences in symptoms among ANFE patients with SZ [38,39].…”
Section: Discussionsupporting
confidence: 79%
“…Cowell et al published one of the earlier studies showing that female patients with SZ receiving clozapine had significantly greater weight gain than male patients [5], and later work has confirmed these sex differences in antipsychotic-induced weight gain [6][7][8].…”
Section: Sex-specific Association Of Antipsychotic-induced Weight Gaimentioning
confidence: 99%
“…Second, we note that the sex ratio is significantly different among the 4 groups. Previous studies [57][58][59] explored the impact of sex differences on the brain features of schizophrenia, but the results are inconsistent, even a study 58 reported no significant differential sex effects in schizophrenia for either GM cortical thickness or subcortical volume development. In this study, we took age and sex as covariates by ANCOVA analysis to control for potential confounding effects and found that sex has no interactive effect on the results.…”
Section: Discussionmentioning
confidence: 99%
“…There are many differences in clinical symptoms, the age of disease onset, and antipsychotic treatment response between male and female SCZ patients [3,[40][41][42]. Abnormal X chromosome function may play an essential role in the sex-related phenotype of SCZ [4].…”
Section: Discussionmentioning
confidence: 99%